IMPLEMENTATION OF THE SILA ALMIGHTY GOD IN DEVELOPMENT OF RELIGIOUS CHARACTER - Muhammad Farhan Maulana; Mubarak Ahmad (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
This study aims to find out how schools apply and cultivate religious character to students. This research uses qualitative methods with case studies. Conduct research using observation procedures, interviews, and documentation studies. The subjects of the study were principals, class teachers, and grade 4 students. To get data on the implementation and development of religious character, researchers interviewed the subject. The conclusion of this study is to find out how schools apply, foster and apply religious character in schools.